Covid-19 pandemic, public policy and institutions in India : issues of labour, income and human development - De, Indranil; Chattopadhyay, Soumyadip; Nathan, Hippu Salk Kristle; Sarkar, Kingshuk (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book looks at the institutional and governance issues faced by India during the first and second wave of the COVID-19 pandemic and its adverse impact on the vulnerable sectors and groups. The book is split into four parts, with preceding chapters informing later ones. Part One outlines the approach of the study, in particular their examination of policy responses and the effect of the pandemic. Part Two delves into the governance challenges in containing the pandemic while giving the theoretical rationale for institutional responses. Part Three looks at how the pandemic affected economically vulnerable households, workers, and small industries. The effect of pandemic on the informal sector is also detailed. Lastly, Part Four examines the impacts and responses of Indian public infrastructure and services to the pandemic, in particular the impact of the COVID-19 pandemic on health care and schooling. It also explores the challenges caused by infrastructure inadequacies in Indian cities. The book closes by looking at how businesses in the private sector have responded to the COVID-19 pandemic, with a focus on Corporate Social Responsibility. The book will be a useful reference to researchers, policymakers, and practitioners who are interested in institutions and development, especially in the context of India"--
Introduction : the COVID-19 pandemic, challenges, and policy / Indranil De, Hippu Salk Kristle Nathan Soumyadip Chattopadhyay, and Kingshuk Sarkar -- Policy response to pandemic : COVID-19 SOPs and guidelines / Shyam Singh -- The dichotomies of management and governance in the COVID-19 pandemic : a view from Rawls difference principle and political economy perspective / Hippu Salk Kristle Nathan and Indranil De -- Some aspects of impact of lockdown in India and the way forward / Surajit Das -- Income shocks and resilience of economic institutions : role of collective organizations / Indranil De, Mubashshir Iqbal and Rooba Hasan -- Plight of migrant informal workers in India and the context of COVID-19 and inadequacy of existing labour legislations / Kingshuk Sarkar -- MSMEs in India during lock and unlock times : policy responses and coping strategies / Soumyadip Chattopadhyay and Partha Pratim Sahu -- The impact of the COVID-19 pandemic on domestic workers in India / Amrita Ghatak and Kingshuk Sarkar -- Infrastructure deficits in Indian cities amid COVID-19 : key opportunities and challenges for policy and practice / Soumyadip Chattopadhyay -- Non-COVID-19 health care under the era of COVID-19 : a study from rural Bengal / Md Sahidul Islam, Hippu Salk Kristle Nathan -- Impact of pandemic on school education in India : generations at risk / Saswati Paik and Roshan M Samuel -- Conspicuous philanthropy or CSR in times of the COVID-19 pandemic / Sudhir Kumar Sinha.
Keywords: COVID-19 Pandemic, 2020- -- India; COVID-19 Pandemic, 2020- -- Social aspects -- India; COVID-19 (Disease) -- Government policy -- India; Medical policy -- India; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Public Policy / Social Policy; EDUCATION / Organizations & Institutions